2002
DOI: 10.1063/1.1448892
|View full text |Cite
|
Sign up to set email alerts
|

Improved interfaces and magnetic properties in spin valves using Ni80Fe20 seed layer

Abstract: The “giant” magnetoresistance (GMR) (Ni80Fe20)O–Co–Cu based “top” spin valves were studied with and without Ni80Fe20 as a seed layer. Microstructure examination shows that without the seed layer, the “free” and the “pinned” Co layers of the spin valves are highly irregular, discontinuous, and connected by pinholes across the Cu spacer layer, resulting in a large coupling >5.96 kA/m (>75 Oe) and a negligible GMR effect (<0.7%). The presence of Ni80Fe20 seed layer leads to continuous layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has been widely reported that the microstructures, especially the textures and roughness of films may affect the magnetic properties significantly [8][9][10], so spin-valve systems are usually grown on thin buffer layers such as Ta, NiFe, Fe, Cu, etc. [11,12]. In addition, the nucleation of deposit on semiconductor usually requires an extra cathodic overpotential [13], which may induce the fluctuation of current flow.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that the microstructures, especially the textures and roughness of films may affect the magnetic properties significantly [8][9][10], so spin-valve systems are usually grown on thin buffer layers such as Ta, NiFe, Fe, Cu, etc. [11,12]. In addition, the nucleation of deposit on semiconductor usually requires an extra cathodic overpotential [13], which may induce the fluctuation of current flow.…”
Section: Introductionmentioning
confidence: 99%